Clinical effects of an oral supplement rich in antioxidants on skin radiance in women - Dumoulin M; Gaudout D; Lemaire B (Dove Medical Press, 2016)
Marion Dumoulin, David Gaudout, Benoit Lemaire Activ’Inside, Libourne, France Background: Environmental factors impact the skin aging resulting in decrease of skin radiance. Nutrition and particularly antioxidants could help to fight against skin degradation.Objective: The aim of this study was to evaluate the effects of an oral supplement rich in specific antioxidants, SkinAx2TM, on the improvement of the skin radiance in women.Methods: The open-label clinical study enrolled 35 women, aged 40–70, with facial dull complexion. Subjects were supplemented orally with a daily dosage of 150 mg of an antioxidant-rich formulation containing superoxide dismutase-rich melon concentrate, grape seed extract rich in monomers of flavanols, vitamin C, and zinc for 8 weeks. Each subject served as her own control. The C.L.B.T.™ test has been used to evaluate facial skin coloring (C), luminosity (L), brightness (B), and transparency (T) involved in skin radiance. Facial skin imperfections have been assessed by clinical assessment. Firmness has been evaluated by clinical assessment and cutometer measurement. Finally, an auto-questionnaire has been carried out in order to evaluate the satisfaction of the subjects concerning different parameters involved in skin radiance and the global efficacy of the supplement.Results: Skin “red pink” and “olive” colors were significantly improved after supplementation (P<0.0001). Luminosity was increased by 25.9% (P<0.0001) whereas brightness and transparency were not affected by the supplementation. Facial skin imperfections were significantly reduced after the antioxidant-rich formulation intake (global reduction: –18.0%; P<0.0001). Indeed, dark circles, redness, and spots significantly diminished after oral treatment. Firmness and elasticity have been shown to be improved. Subjects were globally satisfied by the product (82.4%) and have found improvements on their facial skin. Furthermore, 64.7% reported to look better at the end of the supplementation.Conclusion: The oral supplement containing the antioxidant-rich formulation was found to improve skin radiance by reducing skin coloring, increasing face luminosity, reducing imperfections, and improving skin firmness in women with dull complexion. Keywords: antioxidants, skin radiance, oral supplement, aging, clinical trial